(untitled) (ENTHYMEMA, 2020)
Critics’ inability to cope with the fragmentation of contemporary poetry’s trends may derive from their very own critical repertoires. Starting from this hypothesis, this paper combines insights by Franco Fortini with concepts from Austin’s pragmatics, Silverstein’s linguistic anthropology and Boltanski’s pragmatic sociology, in order to introduce a ‘pragmatic criticism’, that is to say a study of metapragmatic transitions in collections of poetry. Exemplification of usage is then given through poems from Le mie poesie non cambieranno il mondo by Patrizia Cavalli.